Molecular Modeling and In Vitro Studies of a Neutral Oxime as a Potential Reactivator for Acetylcholinesterase Inhibited by Paraoxon - de Paula, Reuel L; de Almeida, Joyce S F D; Cavalcante, Samir F A; Gonçalves, Arlan S; Simas, Alessandro B C; Franca, Tanos C C; Valis, Martin; Kuca, Kamil; Nepovimova, Eugenie; Granjeiro, José M (Molecules (Basel, Switzerland), 2018)
The present work aimed to compare the small, neutral and monoaromatic oxime, isatin-3-oxime (isatin-O), to the commercial ones, pralidoxime (2-PAM) and obidoxime, in a search for a new potential reactivator for acetylcholinesterase (AChE) inhibited by the pesticide paraoxon (AChE/POX) as well as a novel potential scaffold for further synthetic modifications. The multicriteria decision methods (MCDM) allowed the identification of the best docking poses of those molecules inside AChE/POX for further molecular dynamic (MD) studies, while Ellman's modified method enabled in vitro inhibition and reactivation assays. In corroboration with the theoretical studies, our experimental results showed that isatin-O have a reactivation potential capable of overcoming 2-PAM at the initial moments of the assay. Despite not achieving better results than obidoxime, this molecule is promising for being an active neutral oxime with capacity of crossing the blood⁻brain barrier (BBB), to reactivate AChE/POX inside the central and peripheral nervous systems. Moreover, the fact that isatin-O can also act as anticonvulsant makes this molecule a possible multipotent reactivator. Besides, the MCDM method showed to be an accurate method for the selection of the best docking poses generated in the docking studies.
Keywords: Ellman’s method; Models, Molecular; oximy; simulace molekulového dockingu; paraoxon; Erythrocytes; Oximes; Paraoxon; Molecular Docking Simulation; acetylcholinesterase; neutral oxime; molekulární modely; molekulární struktura; cholinesterasové inhibitory; Molecular Structure; simulace molekulární dynamiky; multicriteria decision making; Molecular Dynamics Simulation; TOPSIS-AHP; reaktivátory cholinesterasy; erytrocyty; Cholinesterase Reactivators; molecular modeling; Cholinesterase Inhibitors